(untitled) (Cakrawala - Jurnal Humaniora, 2024)
This study is motivated by the urgent need to formulate a model of Pancasila communication that is relevant to the challenges of the digital era. The values of Pancasila are often limited to normative discourses; therefore, it is necessary to integrate them strategically into contemporary communication practices, particularly through communication philosophy, advertising, and public relations. The purpose of this research is to formulate a Pancasila communication model that internalizes national ideological values while addressing the needs of persuasion, branding, and public relations in the modern era. The study employed a qualitative approach with a constructivist paradigm, utilizing library research and critical discourse analysis. The data sources consisted of official state documents (the 1945 Constitution, founding fathers’ speeches, BPIP documents, the Indonesian Advertising Ethics Code, and Public Relations Code of Ethics), academic literature (journals, books, and proceedings published between 2019–2025), and contextual data such as public communication campaigns, public service advertisements, BPIP digital content, and Pancasila-based CSR practices. The data were analyzed through data reduction, critical discourse analysis, and synthesis into a Pancasila communication model. The findings reveal that integrating Pancasila values with communication philosophy provides a strong conceptual framework for constructing ethical persuasive messages. Advertising practices contribute emotional and rational appeal to the dissemination of Pancasila messages, while public relations functions as a relational mechanism to strengthen public trust. The combination of these three aspects results in a Pancasila communication formulation that both safeguards the nation’s ideology and remains relevant within the digital communication ecosystem. The study concludes that Pancasila communication should not only be perceived as a normative legacy but can also be transformed into a practical communication strategy within modern advertising and public relations. It is recommended that public and private institutions develop communication strategies based on Pancasila values that are transparent, creative, and adaptive to the challenges of the digital era.